Jalili Syndrome: Cross-sectional and Longitudinal Features of Seven Patients With Cone-Rod Dystrophy and Amelogenesis Imperfecta - Hirji, Nashila (Am J Ophthalmol, 2018)
PURPOSE: To characterize a series of 7 patients with cone-rod dystrophy (CORD) and amelogenesis imperfecta (AI) owing to confirmed mutations in CNNM4, first described as “Jalili Syndrome.” DESIGN: Retrospective observational case series. METHODS: Seven patients from 6 families with Jalili Syndrome were identified at 3 tertiary referral centers. We systematically reviewed their available medical records, spectral-domain optical coherence tomography (SD-OCT), fundus autofluorescence imaging (FAF), color fundus photography, and electrophysiological assessments. RESULTS: The mean age at presentation was 6.7 years (range 3-16 years), with 6 male and 1 female patient. CNNM4 mutations were identified in all patients. The mean Snellen best-corrected visual acuity (BCVA) at presentation was 20/246 (range 20/98 to 20/399) in the right eye and 20/252 (range 20/98 to 20/480) in the left. Nystagmus was observed in all 7 patients, and photophobia was present in 6. Funduscopic findings at presentation were variable, ranging from only mild disc pallor to retinal vascular attenuation and macular atrophy. Multimodal imaging demonstrated disease progression in all 7 patients over time. Electroretinography uniformly revealed progressive cone-rod dysfunction. CONCLUSIONS: Jalili Syndrome is a rare CORD associated with AI. We have further characterized its ocular phenotype, including describing SD-OCT, FAF, and electrophysiological features; and report several novel disease-causing sequence variants. Moreover, this study presents novel longitudinal data demonstrating structural and functional progression over time, allowing better informed advice on prognosis.